2018
DOI: 10.1016/j.jacbts.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide Receptor-C Protects Against Angiotensin II-Mediated Sinoatrial Node Disease in Mice

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 72 publications
3
34
0
Order By: Relevance
“…Representative activation maps (Fig. 3A) illustrate that conduction initiates in the right atrial posterior wall and then spreads across the full atrial preparation (21)(22)(23). These representative maps show that total conduction time across the full atrial preparation is longer in Akita mice.…”
Section: Resultsmentioning
confidence: 95%
“…Representative activation maps (Fig. 3A) illustrate that conduction initiates in the right atrial posterior wall and then spreads across the full atrial preparation (21)(22)(23). These representative maps show that total conduction time across the full atrial preparation is longer in Akita mice.…”
Section: Resultsmentioning
confidence: 95%
“…This does not mean that NPR-B cannot be targeted pharmacologically, as recent studies suggest that novel designer peptides that bind to NPR-B can reduce fibroblast proliferation and collagen secretion in vitro and in vivo [128,149,150]. This role of endogenous NPR-C signalling in regulating fibrosis is supported by other studies that have observed greater cardiac dysfunction, atrial collagen deposition, and higher levels of TGFβ and TIMP1 in NPR-C KO mice subjected to angiotensin II-induced pressure overload [151,152]. Furthermore, a functional genetic variant in NPR-C has been discovered in humans that is associated with diastolic dysfunction.…”
Section: Endogenous Cnp Is Cardioprotective In Animal Models Of Hementioning
confidence: 84%
“…Sangaralingham and colleagues also demonstrated that NPR-C may mediate the antifibrotic and antiproliferative peptide CNP in cultured adult human cardiac fibroblasts [46]. Furthermore, we recently showed that mice lacking NPR-C exhibit enhanced collagen expression and deposition in the atria [47,48], whereas selective NPR-C activation may prevent pathological collagen deposition [49]. The activation of NPR-C signaling may inhibit the hypoxia-induced vascular endothelial cell growth factor (VEGF) transcription and protein production, suggesting that this receptor may have both direct [50], and indirect effects as antiproliferation factors for endothelial cells (EC), the latter potentially mediated via modulating VEGF synthesis [51].…”
Section: Npr-c Signaling As a Therapeutic Target In Tissue Remodelingmentioning
confidence: 99%